GEOGRAPHY OF GRAND DAMS AND EMERGENCY SITUATIONS RELATED TO THEM (Scientific journal of the Fergana State University, 2024)
Today in different countries of the world there is an increasing desire to build huge dams in river basins. The main purpose of building large dams is to obtain cheap electricity. This is very important for the development of the country's economy, but it is also obvious that emergency situations that may arise in them will inevitably endanger people's lives. Considered as a huge source of income, the huge losses that can be caused by the construction of these gigantic structures are ignored. To this end, this article highlights the huge dams built by humans and the emergencies associated with them.